Proteotyping of Clostridioides difficile as Alternate Typing Method to Ribotyping Is Able to Distinguish the Ribotypes RT027 and RT176 From Other Ribotypes - Emele, Matthias F.; Joppe, Felix M.; Riedel, Thomas; Overmann, Jörg; Rupnik, Maja; Cooper, Paul; Kusumawati, R. Lia; Berger, Fabian K.; Laukien, Friederike; Zimmermann, Ortrud; Bohne, Wolfgang; Groß, Uwe; et al. (Frontiers in Microbiology, 2019)
Clostridioides difficile, a Gram-positive spore-forming bacterium, is the leading cause of nosocomial diarrhea worldwide and therefore a substantial burden to the healthcare system. During the past decade, the hypervirulent PCR-ribotype (RT) 027 population emerged rapidly all over the world, associated with both, increased severity and mortality rates. It is thus of great importance to identify epidemic strains such as RT027 as fast as possible. While commonly used diagnostic methods, e.g. multi locus sequence typing (MLST) or PCR-ribotyping, are time-consuming, proteotyping offers a fast, inexpensive, and reliable alternative solution. In this study, we established a MALDI-TOF-based typing scheme for C. difficile. A total of 77 ribotyped strains representative for five MLST clades were analyzed by mass spectrometry. MLST, based on whole genome sequences, and PCR-ribotyping were used as reference methods. Isoforms of MS-detectable biomarkers, typically ribosomal proteins, were related with the deduced amino acid sequences and added to the C. difficile proteotyping scheme. In total, we were able to associate nine biomarkers with their encoding genes and include them in our proteotyping scheme. The discriminatory capacity of the C. difficile proteotyping scheme was mainly based on isoforms of L28-M (2 main isoforms), L35-M (4 main isoforms), and S20-M (2 main isoforms) giving rise to at least 16 proteotyping-derived types. In our test population, five of these 16 proteotyping-derived types were detected. These five proteotyping-derived types did not correspond exactly to the included five MLST-based C. difficile clades, nevertheless the subtyping depth of both methods was equivalent. Most importantly, Proteotyping-derived clade B contained only isolates of the hypervirulent RT027. Proteotyping is a stable and easy-to-perform intraspecies typing method and a promising alternative to currently used molecular techniques. It is possible to distinguish RT027 isolates from non-RT027 isolates using proteotyping, providing a valuable diagnostic tool.